The Role of Islamic Social Movements in Indonesia’s Democracy: Activism, Welfare, and Education - Wulandari Wulandari; Jamal Mirdad; Sri Wahyuni; Wendra Yunaldi (Yayasan Adra Karima Hubbi, 2025)
Background. Customary law ('urf) plays a crucial role in shaping Islamic legal thought, particularly in traditional regions where local traditions intersect with Sharia principles. Historically, Islamic jurists have recognized the relevance of customary law in legal deliberations, particularly when it does not conflict with the fundamental texts of the Qur'an and Sunnah. Purpose. This study aims to analyze the integration of customary law within the Islamic legal framework, emphasizing its role in the formulation of legal decisions across time periods and schools of jurisprudence. Methods. This study uses a qualitative research design with a case study approach to explore the role of Islamic social movements in shaping Indonesian democracy, particularly in the areas of activism, welfare, and education. Results. The findings indicate that customary law not only serves as a complementary legal source but also contributes significantly to the contextualization and adaptability of Islamic legal norms across various communities. Furthermore, jurists from the Maliki, Hanafi, and Shafi'i schools have demonstrated varying degrees of acceptance of 'urf, reflecting a dynamic and pluralistic legal tradition. Conclusion. In conclusion, the incorporation of customary law into Islamic jurisprudence underscores the flexibility and responsiveness of Islamic legal theory to local realities.